Diseño de una red wifi Mesh para mejorar la cobertura de internet en áreas de la Facultad de Administración, Finanzas E Informática. - Nájera Ruiz, Denisse Scarleth (2025)
The Faculty of Administration, Finance and Informatics (FAFI) of the Technical University of Babahoyo faces connectivity problems due to an outdated WiFi infrastructure, generating areas with low signal, slowness and frequent interruptions. This considerably affects the academic and administrative process and the general perception of the educational quality of the institution. To solve this problem, it is proposed to implement a wireless network with WiFi Mesh technology, using advanced equipment that will significantly expand the coverage, stability and speed of the internet throughout the faculty. The project includes a detailed analysis of the current situation using specialized tools, as well as a network design based on WiFi Mesh devices capable of optimizing connectivity in critical areas. It was determined that this solution is technically and economically feasible, ensuring not only an immediate improvement but also an adaptable technological platform for future academic and administrative needs.